Mung Bean (Vigna radiata) Microgreens Filtrate Supplementation in Skim Milk Yoghurt Raised Antioxidant Level - Wardani, Nelly Indira Kusuma; Asri, Mahanani Tri (LenteraBio : Berkala Ilmiah Biologi, 2026)
The increasing demand for functional foods supplemented with antioxidants is accelerating the need to enrich skimmed milk yoghurt with mung bean (Vigna radiata) microgreens filtrate, which is rich in bioactive compounds. This study aimed to assess the effect of microgreen filtrate concentration on antioxidant levels with consideration to lactic acid and pH level of the yoghurt, as well as to determine the optimal concentration that increases antioxidant activity without reducing physicochemical quality. The research design used a completely randomized design (CRD) with four filtrate concentrations: 0%, 15%, 20%, and 25%. Antioxidant level was tested using the DPPH method, while lactic acid levels were tested using phenolphthalein. Kolmogorov-Smirnov normality test, one-way ANOVA, and Duncan test were used to analyze the antioxidant levels data. Lactic acid levels and pH were analyzed descriptively, referring to SNI 2981:2009. The results showed that 25% filtrate treatment produced the highest antioxidant levels (75.92 ± 5.12), significantly different from other treatments, while lactic acid levels (0.76-0.89%) and pH (4.80-5.17) remained within quality standards. Results indicated that mung bean microgreens filtrate at 25% concentration increased the skim milk yoghurt’s antioxidant level without affecting the product’s physicochemical quality.